An appraisal of Indonesia's immense peat carbon stock using national peatland maps: uncertainties and potential losses from conversion - Warren, M.; Hergoualc'h, Kristell; Kauffman, J.B.; Murdiyarso, Daniel; Kolka, R. (Springer, 2017)
Background: A large proportion of the world’s tropical peatlands occur in Indonesia where rapid conversion and associated losses of carbon, biodiversity and ecosystem services have brought peatland management to the forefront of Indonesia’s climate mitigation efforts. We evaluated peat volume from two commonly referenced maps of peat distribution and depth published by Wetlands International (WI) and the Indonesian Ministry of Agriculture (MoA), and used regionally specific values of carbon density to calculate carbon stocks.